Bahá'í faith: a guide for the perplexed - Stockman, Robert H. (Guides for the perplexed, 2013)
Founded by Bahá?u?llah in Iran in the 19th century, the Bahá?í Faith is one of the youngest of the world?s major religions. Though it has over 5 million followers worldwide, it is still little understood outside of its own community. The Bahá?í Faith: A Guide for the Perplexed explores the utopian vision of the Bahá?í Faith including its principles for personal spiritual transformation and for the construction of spiritualized marriages, families, Bahá?í communities, and, ultimately, a spiritual world civilization. Aimed at students seeking a thorough understanding of this increasingly studied